Frontispiece: Enantioselective C−H Functionalization Reactions under Gold Catalysis. Issue 20 (6th April 2022) - Das, Avishek; Patil, Nitin T.
Abstract : A comprehensive overview of enantioselective C−H functionalization reactions under gold catalysis is given. These transformations have been achieved by employing 1) the chiral gold complexes, and 2) achiral gold complexes along with chiral amines or chiral Brønsted acids. Read more in the Review by A. Das and N. T. Patil (DOI: 10.1002/chem.202104371 ).